Golgi stress response: A regulatory mechanism of Golgi function. (9th September 2021) - Gao, Jiayin; Gao, Anbo; Liu, Wei; Chen, Linxi
Abstract: The organelle of eukaryotes is a finely regulated system. Once disturbed, it activates the specific autoregulatory systems, namely, organelle autoregulation. Among which, the Golgi stress response accounts for one. When the abundance and capacity of the Golgi apparatus are insufficient compared with cellular demand, the Golgi stress response is activated to enhance the function of the Golgi apparatus. Although the molecular mechanism of the Golgi stress response has not been well characterized yet, it seems to be an important part of the mammalian stress response. In this review, we discuss the current status of research on the six pathways of the mammalian Golgi stress response (the TFE3, heat shock protein 47, CREB3, E26 transformation specific, proteoglycan, and mucin pathways), which regulate the general function of the Golgi apparatus, anti‐apoptosis, pro‐apoptosis, proteoglycan glycosylation, and mucin glycosylation, respectively.